Peran Militer Sebagai Pelindung Rakyat Indonesia Pada Saat Negara Dalam Keadaan Darurat Ditinjau dari Perspektif Militer (Berdasarkan Kejadian Gerakan Aceh Merdeka) - Kirana Ardhelia Putri; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In emergency situations, the military's role becomes important and has a major impact on the security, stability and survival of a nation. Emergencies can take the form of war, natural disasters, internal conflicts or serious threats to national security. The military's role is primarily to maintain national security and state sovereignty. Therefore, clear laws and good governance are needed to ensure the military's role in emergency situations is carried out based on the principles of justice, transparency and accountability. In this research, normative legal research is used. Where normative legal research is done by researching materials in libraries or secondary data. In the Indonesian state constitution, it is briefly stated about how to determine the state when it is in a state of emergency. As an implementation of the constitutional mandate, Government Regulation in Lieu of Law (Perpu) Number 23 of 1959 was issued (Government Regulation in Lieu of Law (Perpu) Number 23 of 1959 concerning the Revocation of Law Number 74 of 1957 (State Gazette Number 160 of 1957) And Determination of a State of Danger. This law also covers the entire role of the military if the country is in a state of emergency, whether civil, military or war. The military, as stated in the law, takes a fairly large part in handling emergencies. The military's role during the conflict has been the focus of debate regarding its activities, policies and impact on the people of Aceh. The TNI's role in the Aceh war was, among other things, a response to GAM activities accused of separatism. Military operations include military security operations and anti-military policies.